Quotients of Essentially Euclidean Spaces. Issue 1 (9th January 2019) - Figiel, Tadeusz; Johnson, William
Abstract: A precise quantitative version of the following qualitative statement is proved: If a finite-dimensional normed space contains approximately Euclidean subspaces of all proportional dimensions, then every proportional dimensional quotient space has the same property.